High-speed characterization of two-phase flow and bubble dynamics in titanium felt porous media for hydrogen production. (20th February 2021) - Li, Yifan; Yang, Gaoqiang; Yu, Shule; Mo, Jingke; Li, Kui; Xie, Zhiqiang; Ding, Lei; Wang, Weitian; Zhang, Feng-Yuan
Highlights: Rapid two-phase flow and micro oxygen bubble dynamics are in-situ visualized. Bubble detachment diameters and frequencies increase with current density. GDL structures and morphologies has a great impact on micro bubble detachments. Slug flow tends to form at high current densities and low flow velocities. Abstract: Bubble dynamics and two-phase flow phenomena are closely related to the performance of proton exchange membrane electrolyzer cells (PEMECs). This paper reports an in-situ study of the oxygen bubble behavior and associated multiphase evolutions in the anode side of PEMECs with titanium (Ti) felt liquid gas diffusion layers (LGDLs) by a high-speed visualization system. The micro oxygen bubble dynamics was captured and analyzed at different locations and virous operating conditions. The results show that the bubble detachment frequency and detachment diameter greatly increase with the operating current density. Additionally, they are significantly impacted by the local pore structure and morphology of Ti felt LGDLs. In the flow channels, there exist only several discrete micro bubbles at a low current density (0.04 A/cm 2 ) and a large flow velocity (133 mm/s). At a current density (0.2 A/cm 2 ) and a flow velocity (67 mm/s), a number of gas slugs are formed in the follow channels, in addition to discrete micro bubbles. At a high current density (1 A/cm 2 ) and a flow velocity (67 mm/s), more bubbles appear in the channel, and the flow field is dominated by slug or annular flows. These investigations can help to better understand the two-phase flow and bubble detachment mechanism, and provide a foundation for electrochemical reaction, multiphase flow studies and optimize the design of gas diffusion layers and flow fields for PEMECs in the future.